Representation theory of finite groups and finite-dimensional algebras: proceedings of the Conference at the University of Bielefeld from May 15-17, 1991, and 7 Survey Articles on Topics of Representation Theory - Michler, Gerhard O. (Springer Basel AG, 1991)
1. Survey Articles: -- Clifford-Matrices -- Research in Representation Theory at Mainz (1984-1990) -- Computational Aspects of Representation Theory -- Der Kenntnisstand in der konstruktiven Galoisschen Theorie -- Contributions to Modular Representation Theory of Finite Groups -- Recent Advances in the Representation Theory of Finite Dimensional Algebras -- The isomorphism problem for integral group rings of finite groups -- 2. Research Articles: -- Cohen-Macaulay and Gorenstein Artin Algebras -- Classical Invariants and the General Linear Group -- Partial characters of ?-separable groups -- First Cohomology Groups for Classical Lie Algebras -- Endotrivial modules and the Auslander-Reiten quiver -- Tame curve singularities with large conductor -- Polynomial representations of finite general linear groups in non-describing characteristic -- On Auslander-Reiten components for wild blocks -- On Gorenstein Algebras -- Decomposition numbers of finite groups of Lie type in non-defining characteristic -- Counting blocks of defect zero -- Group-theoretical descriptions of ring-theoretical invariants of group algebras -- Darstellungstheoretische Methoden bei der Realisierung einfacher Gruppen vom Lie Typ als Galoisgruppen -- Some new developments and open questions in the character theory of finite groups -- Some applications of representation theory -- A construction of orders of finite global dimensions -- Duality and forms in representation theory.
Keywords: Konferenzschrift